2017
DOI: 10.1080/10408398.2016.1230089
|View full text |Cite
|
Sign up to set email alerts
|

Dietary total antioxidant capacity as a tool in health outcomes in middle-aged and older adults: A systematic review

Abstract: The dietary total antioxidant capacity (TAC) has been a useful tool in epidemiological studies. To assess whether the TAC is associated with chronic diseases in middle-aged and older adults carried out a systematic review of articles indexed in MEDLINE and Science Direct. Of the 104 articles found, nine were included to meet the inclusion criteria. There was variation among the items on the sample size, sample origin, use of statistical tests, analysis of different outcomes and the use of assays to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Several studies found an inverse relationship between dietary total antioxidant capacity (DTAC) and the risk of chronic diseases in aging people. A meta-analysis of those data concluded that DTAC has a great potential for clinical applications and public health [ 24 ]. Previously, we found a diminished DTAC value in an elderly population, and particularly in the elderly women, compared to that in the young and middle-aged subjects [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found an inverse relationship between dietary total antioxidant capacity (DTAC) and the risk of chronic diseases in aging people. A meta-analysis of those data concluded that DTAC has a great potential for clinical applications and public health [ 24 ]. Previously, we found a diminished DTAC value in an elderly population, and particularly in the elderly women, compared to that in the young and middle-aged subjects [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary total antioxidant capacity (DTAC) is an indicator of diet quality which is used to estimate the cumulative power of antioxidants in the whole diet [14]. Recently, DTAC is described as an effective tool for determining the health outcomes in middle-aged and elderly populations [15].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary total antioxidant capacity (DTAC) is a novel indicator of diet quality [40], which is used to estimate the cumulative power of antioxidants in the whole diet [41]. Recently, DTAC is described as an effective tool for determining the health outcomes in populations [42,43]. This new approach could serve for future lines of research to understand the behavior and association of uric acid, antioxidant status and diet in these patients [44].…”
Section: Discussionmentioning
confidence: 99%